(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Background: Understanding the three-dimensional (3D) anatomical relationships of the renal arterial system and the renal pelvis-calyx complex is essential for improving surgical planning and reducing complications in urological procedures. Objective: The purpose of the study was to reveal the patterns of the three-dimensional quantitative organization of the branches of the renal artery in relation to the elements of the renal pelvis-calyx system in women. Methodology: The study was conducted on 64 corrosion specimens of kidneys from deceased women aged 22 to 75 years who died of causes unrelated to the urinary system. Extra-organ and intra-organ branches of the renal arteries were identified and analyzed in relation to the frontal, horizontal, and sagittal planes. Quantitative-morphological analysis was performed on kidneys with two, three, and four excretory sectors. Data were processed using variation statistics methods with Microsoft Excel. Age-related differences were examined across mature, elderly, and senile groups. Results: The renal artery, in the majority of instances, divides into a pair of branches (20, 22.0% of cases across age groups), while it splits into three branches and shows superior/inferior variants with less frequency (3, 5.0%). Across all age demographics, 15.2% of cases systematically manifested both anterior and also posterior pelvic branching. Spatial analysis indicated anterior, posterior branching predominated inside two-sector kidneys (75, 80%), anterior, posterior including upper, lower divisions remained equally represented throughout three-sector kidneys, and anterior, posterior branching prevailed beyond 77.0% of cases throughout four-sector kidneys. Statistically meaningful age-related disparities remained unidentified. Conclusion: The study evinces that when one scrutinizes 3D renal artery branching patterns quantitatively, the analysis furnishes clinically valuable preoperative planning information for women as well as strengthens the accurate visualization and modeling tools’ development to improve diagnostic precision and surgical safety. Bangladesh Journal of Infectious Diseases, June 2025;12(1):93-98